Autoantibody Selectively Inhibits Binding of von Willebrand Factor to Glycoprotein Ib. Recognition Site Is Located in the A1 Loop of von Willebrand Factor - Mohri, Hiroshi; Yamazaki, Etsuko; Suzuki, Zekou; Takano, Toshikuni; Yokota, Shumpei; Okubo, Takao (Thrombosis and Haemostasis, 1997)
A 20-year-old man with severe von Willebrand disease recently presented a progressive bleeding tendency, characterized recurrent subcutaneous hemorrhages and cerebral hemorrhage. Mixing and infusion studies suggested the presence of an inhibitor directed against vWF:RCo activity of von Willebrand factor (vWF) without significant inhibition of the FVIII:C. The inhibitor was identified as an antibody of IgG class. The inhibitor inhibited the interaction of vWF in the presence of ristocetin and that of asialo-vWF with GPIb while it partially blocked botrocetin-mediated interaction of vWF to GPIb. The inhibitor reacted with native vWF, the 39/34kDa fragment (amino acids [aa] 480/ 481-718) and the recombinant vWF fragment (MalE-rvWF508-704), but not with Fragment III-T2 (heavy chains, aa 273-511; light chains, aa 674-728). A synthetic peptide (aa 514-542) did not inhibit vWF-inhibitor complex formation. We conclude that this is the first autoantibody of class IgG from human origin that recognizes the sequence in the A1 loop of vWF, resulting in a virtual absence of functional vWF and a concomitant severe bleeding tendency although recognition site is different from the residues 514-542 which is crucial for vWF-GPIb interaction.